Efeito do Treinamento de Habilidades baseado em simulação na ansiedade e autoconfiança dos estudantes de Medicina em relação ao exame pélvico e de mamas - ORSI, T. D. (2018)
Introduction: The use of mannequin simulation in the learning of gynecology has become important in medical graduation in order to prepare students to perform the gynecological examination with confidence, competence, and reduction of anxiety. Objective: To evaluate the effect of simulation-based educational activity on anxiety and self-confidence concern pelvic and breast exam. Methods: A longitudinal quantitative study with 80 students was applied to fourth-grade medical students from José do Rosário Vellano University / UNIFENAS, campus Alfenas, who responded to questionnaires prior and post simulation-based training (THBS) in gynecology and obstetrics. The questionnaires were divided into socio-demographic questions, anxiety questions before and after practice, and satisfaction and self-confidence questions after the educational activity. Results: 72 students, mostly women, were included and it was observed that the students' anxiety as to pelvic exam was greater than that of breast examination (p <0.001). There was no statistically significant difference in baseline anxiety between males and females in the pelvic examination, breast examination and overall anxiety scores. The main reason for the students' basal anxiety about pelvic examination was their fear of hurting the patient, followed by the fact that they had never attended a pelvic exam before. The THBS significantly reduced students’ anxiety concerning to pelvic and breast examination with no difference between the sexes (2.04 vs. 1.46, respectively, p <0.001). Students satisfaction and self-confidence were high (98,75% and 71,7%, respectively), with no difference between the sexes. Conclusion: The THBS educational activity is a learning model that favors the reduction of anxiety and elevates the students’ satisfaction and self-confidence in performing the gynecological examination with no differences between the sexes.